Electrodeposition of CuInSe2 thin film for photovoltaic application - Tantiono, Handiyadi. (2012)
Copper indium diselenide (CuInSe2) is one of the most promising materials for solar cell today. To date, the highest solar cell efficiency achieved by this material is 20.3%. However, realization of this technology is usually hindered by the expensive vacuum production method. Electrodeposition of CuInSe2 provides a promising non-vacuum method for solar cells large-scale production with great scalability and cost-minimization. However, the wide cathodic deposition potentials difference between Cu, In and Se gives rise to the formation of unwanted secondary phases on the electrodeposited films. One of the widely known solutions to mitigate this issue is by the incorporation of complexing agents. In this project, the effect of incorporation of oxalic acid, sulfamic acid and diluted HCl as complexing agents into the electrolyte bath will be presented. The deposition potential is limited in a range of -0.60V to -1.00V at 10 minutes deposition time per sample. Subsequently, the samples were characterized by employing Scanning Electron Microscope (SEM), X-Ray Diffractometer (XRD) and Energy Dispersive X-Ray Spectrometer (EDX). First, the effect of deposition potential was analyzed. Then, it was observed that oxalic acid had produced the best film uniformity and crystallinity. However, the stability of the electrolyte bath could only be sustained for 40-50 minutes per deposition. Therefore, sulfamic acid was looked upon as a great alternative. Stabilization of sulfamic acid was even prolonged with the incorporation of Potassium Biphthalate (KHP). It was found that increase in KHP concentration boosted the stability as well as affected the morphology of the samples. Finally, potential future developments of this project will be proposed.